Tales from a not-so-graceful ice princess - Russell, Rachel Renée (Russell, Rachel Renée. Dork diaries, 2012)
Nikki Maxwell is determined to help out her crush Brandon save an animal shelter. So Nikki and her friends Chloe and Zoey enter an ice skating competition to help raise money for the shelter, but (big surprise) Mackenzie has to stick her nose in and cause trouble.